Development of Gluten-Free Dried Noodles with the Addition of Anchovy Protein (Stolephorus insularis) - Evan Michael Ariyanto; Yuyun Yuniati; Adhania Andhika Prayudanti (Green Publisher Indonesia, 2026)
Manufacturer of protein-enriched gluten-free dry noodles This research aims to develop the formulation and manufacture of protein-enriched gluten-free noodles using rice flour as the main base ingredient with the addition of anchovy protein (Stolephorus insularis) in flour. The demand for high-quality, high-protein gluten-free products is increasing rapidly. This is mainly due to the emergence of public awareness about the importance of maintaining health. The anchovies used in this study have been identified as one of the high-quality and economical sources of animal protein. The method includes the characterization of anchovy proteins, and the evaluation of the final product. Using a hedonic test, the results of the study are expected to show the optimal formulation of gluten-free dry noodles that have a significant increase in protein content without sacrificing texture quality and public acceptance. Based on the effectiveness test of the De Garmo method, the A2 treatment was selected as the best treatment with a total result value of 0.642.